Stress, Anxiety, And Depression Among Medical Students Of The CBME Curriculum - George, Alan; Kumar B, Kishor; Mathew, Abey (International Journal of Psychosocial Rehabilitation, 2020)
Medical education has been reported to be one of the most stressful academic curricula worldwide, negatively affecting the physical and mental health of medical students. Examination fear, high parental expectations, peer pressure, lack of leisure time, financial problems, relationship disharmony, and aspirations for higher studies are some of the many factors known to contribute to the development of stress among undergraduate medical students. Early identification and necessary interventions targeting the alleviation of modifiable stressors might result in a less stressful academic life for students, which in turn could enhance their academic performance and skill development as medical graduates.1 Recently National Medical Council of India(NMC) introduced a new educational strategy for medical students by the name of Competency-based medical education(CBME), as it should reduce stress and may increase the efficacy and efficiency of medical students. It has been observed that medical school environments in India are extremely stressful and has led to suicidal attempts by the students. Fear of failure, vast amount of content that has to be mastered, inability to cope with the high expectations of parents and peers are found to be the most commonly observed sources of stress.2 Stress, health and emotional problems increase during the period of undergraduate medical education. This can lead to mental distress and has a negative impact on cognitive functioning and learning. An optimal level of stress, referred to earlier as ‘favourable stress’, can enhance learning. However, excessive stress can lead to physical and mental health problems. It can reduce students’ self-esteem and may affect academic achievement and personal or professional development.3 Stress is the “wear and tear” our bodies experience as we adjust to our continually changing environment; it has physical and emotional effects and can create a positive or negative influence on us. As a positive influence, stress can help to compel us to action. As a negative influence, it can result in feelings of distress, rejection, anger, and depression, which in turn can lead to health problems.4 Chronic exposure to stressful conditions exerts negative effects on the emotional, mental and physical well-being of the students which also affect the patients’ lives and the community’s health. Numerous studies have revealed that persistent stressful conditions are associated with mental and physical health problems in medical students at various stages of their training.5 Anxiety is a general state of uneasiness that cause nervousness, fear, apprehension, and worrying. It is a bodily response to a perceived danger or threat that could be real or imagined and triggered by an individual’s thoughts beliefs and feelings. These disorders affect how we feel and behave, and they can manifest real physical symptoms. People often experience a general state of worry or fear in their routine life before confronting something challenging such as an examination, competition, social encounter or interview, etc. These feelings are easily justified and considered normal. Anxiety is considered a problem when symptoms interfere with a person’s ability to sleep or otherwise function. Generally speaking, anxiety occurs when a reaction is out of proportion with what might be normally expected in a situation. Mild anxiety is vague and unsettling, while severe anxiety can be debilitating, having a serious impact on daily life.6 Depression is a major public health problem with a prevalence of 4.4% in the global population. Globally, individuals with depression are nearly 33 times more likely to commit suicide, while the odds of committing suicide in individuals with depression are about 12 times. Depression is the leading cause of suicide, resulting in close to 800,000 deaths annually (WHO). Medical students have a higher prevalence of depression compared to the general population, despite similar rates of help-seeking behaviours, which may suggest that there may be under-treatment among them. Several reasons have been given for the failure to seek treatment. These include fear of having mental health record and its impact on a future career, tight schedules, the stigma associated with accessing mental healthcare services, and even fear of perceived unwanted interventions. This consequently, may lead to higher rates of suicidal behaviours among medical students, for which a large multi-institution study reported a prevalence of 11.2% of suicidal ideation. Depression among medical students affects their academic performance, clinical practice, and rates of dropout; and may also influence the overall care given to patients as depressed medical students may show less empathy and less willingness to manage chronically ill patients.7 Depressive disorders are characterized by sadness, loss of interest or pleasure, feelings of guilt or low self-worth, disturbed sleep or appetite, feelings of tiredness, and poor concentration. Depression can be long-lasting or recurrent, mild or severe, substantially impairing an individual’s ability to function at work or school or cope with daily life (WHO). At its most severe form, depression can lead to suicide.8 Many studies support the fact that medical students experience depression at higher rates than graduate students or young adults in the general public.9 However, there is very little literature available regarding the prevalence of depressive disorders among medical students in India.10 Medical students are exposed to tremendous pressure, leading to stress, depression and other psychiatric disorder at increasingly higher rates. The stress and depression can affect their learning and can lead to poor quality of life. The students of different professional year may have differing reasons for being under stress and in depression. Assessing stress and depression in students of different professional years may provide better insights, and help policy makers plan appropriate interventions11 Mental health disorders according to the World Health Organization (WHO) are one of the leading causes of disability worldwide. Three of the ten leading causes of disability in people between the ages of 15 and 44 are mental disorders, and the other causes are often associated with mental disorders. Stress is anything that poses a challenge or a threat to our well-being. It has been defined as a process in which environmental demands exceed the adaptive capacity of an organism, resulting in psychological and biological changes that may place persons at risk for disease. Anxiety is a psychological and physiological state characterized by cognitive, somatic, emotional, and behavioural components. These components combine to create an unpleasant feeling that is typically associated with uneasiness, fear, or worry. Anxiety is a generalized mood condition that occurs without an identifiable triggering stimulus, while many symptoms of depression include, persistent sad, anxious or ‘‘empty” feelings, feelings of hopelessness, feelings of guilt, worthlessness and/or helplessness, irritability, restlessness, and loss of interest in activities or hobbies once pleasurable.12 Although the prevalence of depression, anxiety, and stress of medical students has been extensively studied, the percentage remains high and has not been fully addressed. This might occur because students are challenged to live independently so they tend to have fewer places to tell and express their daily stressors13. Professional consequences include academic performance decay, decline in empathy and ethics, academic dishonesty, negative influence on their choice of specialty and high incidence of medical errors.14 Depression and anxiety are common among medical students across the world. In India, a recent systematic review revealed that the pooled prevalence of depression among medical students was 39.2%, and the corresponding figure for anxiety was 34.5%. The prevalence of depression and anxiety disorders in medical students is higher than that in the general population. Despite the severalfold higher prevalence of depression and anxiety disorders among medical students, they do not readily seek treatment. Steps taken to identify and address the barriers to mental healthcare seeking would help improve the students’ mental well-being.15